The Technique of Silence in The Performance of Theatrical Actor: (The Saeat Alsawda play as a model) - Haidar, Samir Agha; Kadhim, Thaer Bahaa (Al-Adab Journal, 2023)
This research concerns in study the technique of silence in the Diction of theatrical actor .The first chapter include the method frame of the research through the research problem , its importance , objective , limits and determine the research terms ,the technique of silence ,the actor recitation .The second chapter includes the theoretical frame and previous studies .The researcher discuses in the first enquiry the technique of silence in theatrical performance through following this technique in Greek, Romantic , Middle Ages and Renaissance .Also it shed a light on the comedy, Delartiee, Pantomime and Mime as the two prominent examples of using this technique .In the second enquiry ,discuss the work of the technique of silence in the actor recitation where the researcher review the most important mechanisms and functions that the silence achieved as a technique in recitation and its collaboration with the voice performance of the actor through two levels. The first is when the silence is productive in itself and the second when it becomes in the form of artistic or psychological intervals. Then the researcher review the most prominent previous studies to conclude what the theoretical frame results of indications .In the third chapter we have the research procedures in which the research sample is determined, the reasons behind choosing the research sample, the research description methodology as well as depend on the indications results of theoretical frame as an instrument for analysis for the example in Sa'at Elsooda (Saeat Alsawda)play that were performed on 2018 .In the fourth chapter the researcher reached to the results , conclusions, recommendations an suggestions concerning the research subject .Then followed by the references and the resources, The most important result of the research: 1-The technique of silence in the recitation of theatrical actor achieved two levels in function. The first when the silence in itself and the second when the silence in the artistic and psychological intervals. 2- The technique of silence represented in the actor throwing in the theatrical performance some of the communicative functions in the verbal dialogue such as repetition, emphasis, linkage, organization and contradiction.